Relationship between Angiogenic Squamous Dysplasia and Bronchogenic Carcinoma in Patients Undergoing White Light Bronchoscopy - Shirin Karimi; Forouzan Mohammadi; Kian Khodadad; Makan Sadr; Leila Seyfollahi; Mohammad Reza Masjedi (Canadian Respiratory Journal)
OBJECTIVE: To better understand the characteristic morphology of angiogenic squamous dysplasia (ASD) and its association with different types of common bronchogenic carcinomas using routine white light bronchoscopy.